The Cambridge handbook of endangered languages - Austin, Peter; Sallabank, Julia (Cambridge handbooks in linguistics., 2011)
"It is generally agreed that about 7,000 languages are spoken across the world today and at least half may no longer be spoken by the end of this century. This state-of-the-art Handbook examines the reasons behind this dramatic loss of linguistic diversity, why it matters, and what can be done to document and support endangered languages. The volume is relevant not only to researchers in language endangerment, language shift and language death, but to anyone interested in the languages and cultures of the world. It is accessible both to specialists and non-specialists: researchers will find cutting-edge contributions from acknowledged experts in their fields, while students, activists and other interested readers will find a wealth of readable yet thorough and up-to-date information"--